Orchestration of Work and Play Within Families. - Primeau, Loree A. (American Journal of Occupational Therapy, 1998)
Objectives. Parental occupations within families include parents' participation in household work and in play with their children. This study explored the nature of parents' play with their preschool-aged children and how it was orchestrated within their daily occupations. Method. Participant observations and intensive interviews were conducted with 10 families with preschool-aged children. Data were analyzed with a grounded theory approach. Results. Parents used two types of strategies to orchestrate work and play in their families: Strategies of segregation resulted in play interspersed with household work, and strategies of inclusion resulted in play embedded in household work. Conclusion. This study identified the process of occupational scaffolding through which parents foster their children's competence as adults; the need for deconstruction of the notion of work and play as separate experiences; and new ideas to guide occupational therapy practice with parents who are juggling paid work, household work, and time with their children.